A feasibility study of neoadjuvant talazoparib for operable breast cancer patients with a germline BRCA mutation demonstrates marked activity. (December 2017) - Litton, J.; Scoggins, M.; Ramirez, D.; Murthy, R.; Whitman, G.; Hess, K.; Adrada, B.; Moulder, S.; Barcenas, C.; Valero, V.; Gomez, J.; Mittendorf, E.; et al.
Abstract This study was undertaken to determine the feasibility of enrolling breast cancer patients on a single-agent-targeted therapy trial before neoadjuvant chemotherapy. Specifically, we evaluated talazoparib in patients harboring a deleterious BRCA mutation (BRCA+). Patients with a germline BRCA mutation and ≥1 cm, HER2-negative primary tumors were eligible. Study participants underwent a pretreatment biopsy, 2 months of talazoparib, off-study core biopsy, anthracycline, and taxane-based chemotherapy ± carboplatin, followed by surgery. Volumetric changes in tumor size were determined by ultrasound at 1 and 2 months of therapy. Success was defined as 20 patients accrued within 2 years and <33% experienced a grade 4 toxicity. The study was stopped early after 13 patients (BRCA 1 + n = 10;BRCA 2 + n = 3) were accrued within 8 months with no grade 4 toxicities and only one patient requiring dose reduction due to grade 3 neutropenia. The median age was 40 years (range 25–55) and clinical stage included I (n = 2), II (n = 9), and III (n = 2). Most tumors (n = 9) were hormone receptor-negative, and one of these was metaplastic. Decreases in tumor volume occurred in all patients following 2 months of talazoparib; the median was 88% (range 30–98%). Common toxicities were neutropenia, anemia, thrombocytopenia, nausea, dizziness, and fatigue. Single-agent-targeted therapy trials are feasible in BRCA+ patients. Given the rapid rate of accrual, profound response and favorable toxicity profile, the feasibility study was modified into a phase II study to determine pathologic complete response rates after 4–6 months of single-agent talazoparib. Therapeutics: PARP inhibitor looks promising ahead of surgery An investigational PARP inhibitor seems safe and possibly effective when given ahead of surgery to women withBRCA -mutated breast cancer. Jennifer Litton and colleagues from the University of Texas MD Anderson Cancer Center in Houston, USA, conducted a small feasibility study to see if patients with stage I-III breast cancer and inherited mutations inBRCA1 orBRCA2 would put off their standard course of chemotherapy ahead of surgery to first receive two months of talazoparib, an experimental inhibitor of poly ADP ribose polymerase (PARP), an enzyme involved in DNA damage repair. The trial was a resounding success. In fact, owing to rapid patient enrollment, decreases in tumor volume among all 13 participants and few signs of serious side effects, the researchers amended the study protocol to give talazoparib for longer and test for therapeutic efficacy.